(untitled) (European Journal of Health Research, 2021)
The contingency generated from the Covid-19 pandemic means that the working conditions of teachers are transformed with an increase in the hours worked, immobility of the workplace, resolution of administrative situations of the educational institution and support for students with Situations that require it, leads to a physical and mental overload on the part of university teachers. A phenomenological design study is developed in which 178 university teachers of the 2020-I cycle are included with a part-time employment contract (4 hours) in the morning-night hours and a full-time employment contract (8 hours); who are working from their homes in theoretical, practical and theoretical-practical methodology. It is found that teachers show impairment in their physical and mental load due to the Covid-19 pandemic contingency, relating the working day, work intensity, interpersonal relationships with respect to the different types of loads from habituality to the given special context Due to contingency, where physical-mental effort, stressful situations in work and non-work activities are factors attributed to the professional burnout of the teacher, the virtual modality has generated that teachers have changing physical and psychological behaviors.